PENGARUH LATIHAN PUSH UP TERHADAP KEKUATAN OTOT LENGAN PADA TIM PANJAT TEBING PUTRA (BOULDER ) FPTI KABUPATEN KARIMUN - Ari Gustiyar; Zainur Zainur; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: Based on observations made in the field during training and competing before the covid-19 virus, researchers saw that there was still a need to improve the athlete's arm muscle strength for the better. This study aims to determine the effect of Push Up Exercise on Arm Muscle Strength in the Men's Rock Climbing Team (Boulder) FPTI Karimun Regency. In this study, the population used was Karimun rock climbing athletes, totaling 10 people. The sampling technique used total sampling so that the sample consisted of 10 athletes. The instrument in this research is an expanding dynamometer. The collected results will be analyzed using the t-test. Based on the t-test produces tcount of 4.955 with ttable of 1.796, then H_a is rejected, at the level of alpha (α) 0.05. It can be concluded that there is an effect of Push Up Exercise on Arm Muscle Strength in the Men's Rock Climbing Team (Boulder) FPTI Karimun Regency.Key Words; Push-ups, Arm Muscle Strength